1999
DOI: 10.1155/dte.5.175
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Photodynamic Therapy in Gastric Cancer

Abstract: Progress of photodynamic therapy (PDT) in gastric cancer and the clinical outcome are described in this paper. (1) We included the whole lesion and a 5 mm margin in the field for irradiation. Marking by injection of India-ink showing the irradiation field was performed beforehand. (2) We established the standard light dose to be 90 J/cm2 for an argon dye laser and 60 J/cm2 for a pulse wave laser. (3) The size of cancerous lesion curable by PDT was expanded from 3 cm in diameter, i.e. 7 cm2 in area to 4 cm in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…In recent years, photodynamic therapy (PDT) using a photosensitizing agent and several light sources has been shown to have nonspecific effects upon malignant diseases. Considerable antitumor effects of PDT have been demonstrated in patients with superficial cancers such as central-type early-stage lung cancer, early-stage gastric cancer, skin cancer, mucosal intraepithelial neoplasia, melanoma, and prostate cancer [1]- [4].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, photodynamic therapy (PDT) using a photosensitizing agent and several light sources has been shown to have nonspecific effects upon malignant diseases. Considerable antitumor effects of PDT have been demonstrated in patients with superficial cancers such as central-type early-stage lung cancer, early-stage gastric cancer, skin cancer, mucosal intraepithelial neoplasia, melanoma, and prostate cancer [1]- [4].…”
Section: Introductionmentioning
confidence: 99%
“…A photosensitizer, such as Photofrin®, accumulates in proliferative tissues such as tumors. After accumulation, the photosensitizer is activated by visible light and induces the generation of singlet oxygen, which damages unwanted cells 5–10. Over the past decade, there have been an increasing number of reports on therapeutic applications of PDT for bacterial infections, especially for infections with multidrug‐resistant bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a promising therapeutic modality for proliferating diseases. A photosensitizer, such as Photofrin ® , accumulates in proliferating cells such as cancer cells and is activated by visible light, resulting in the generation of singlet oxygen, which damages proliferative tissue (5–9). A photosensitizer also accumulates in inflammatory lesions as well as proliferating tissues (10), and it has been reported that the therapeutic efficacy of PDT is achieved by efficient accumulation in infectious lesions of bacteria.…”
Section: Introductionmentioning
confidence: 99%